2023
DOI: 10.1186/s12916-023-02731-y
|View full text |Cite
|
Sign up to set email alerts
|

The effect of maternal BMI, smoking and alcohol on congenital heart diseases: a Mendelian randomisation study

Abstract: Background Congenital heart diseases (CHDs) remain a significant cause of infant morbidity and mortality. Epidemiological studies have explored maternal risk factors for offspring CHDs, but few have used genetic epidemiology methods to improve causal inference. Methods Three birth cohorts, including 65,510 mother/offspring pairs (N = 562 CHD cases) were included. We used Mendelian randomisation (MR) analyses to explore the effects of genetically pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…Other covariates were collected based on existing literature [28][29][30][31], including sex, maternal age at pregnancy, residence, last year's household income, maternal schooling years, pregestational BMI, history of adverse pregnancy outcomes, history of familial congenital malformations, consanguineous marriages, gestational hypertension during this pregnancy, gestational diabetes mellitus during this pregnancy, lifestyle factors during the first trimester of pregnancy (i.e., smoke and drink alcohols), pregestational folic acid supplementation, and pregestational exposure to antibiotics. A portion of the above questions were documented in the nationwide free prenatal health care system [32].…”
Section: Variablesmentioning
confidence: 99%
“…Other covariates were collected based on existing literature [28][29][30][31], including sex, maternal age at pregnancy, residence, last year's household income, maternal schooling years, pregestational BMI, history of adverse pregnancy outcomes, history of familial congenital malformations, consanguineous marriages, gestational hypertension during this pregnancy, gestational diabetes mellitus during this pregnancy, lifestyle factors during the first trimester of pregnancy (i.e., smoke and drink alcohols), pregestational folic acid supplementation, and pregestational exposure to antibiotics. A portion of the above questions were documented in the nationwide free prenatal health care system [32].…”
Section: Variablesmentioning
confidence: 99%
“…Similarly, a systematic review of 24 studies revealed a dose-dependent relationship between maternal overweight, mild and severe obesity, and the incidence of all types of CHDs in offspring [25]. However, a Mendelian randomization study did not demonstrate a causal association between maternal BMI and the incidence of CHDs in offspring [26]. The conflicting results of these studies suggest that the effect of maternal obesity on the offspring's heart remains uncertain, and additional robust evidence and analytical methods are necessary to control for potential confounding factors.…”
Section: Maternal Obesitymentioning
confidence: 99%
“…Acetaminophen and ibuprofen may successfully close the venous hole in the PDA and may be effective for treating other defects, such as VSD(8, 9); however, the most useful method for treating TOF is surgery. Changes in maternal factors during pregnancy can be useful both as a treatment and as a diagnostic method, as a lower concentration of folate in the mother's body during pregnancy is considered an indicator of a greater incidence of CHD (10,11). Reduction of growth factors is another change that can be introduced as the main pathology of CHD in addition to potential therapy.…”
Section: Introductionmentioning
confidence: 99%